Influence of location and promotion on consumer purchase decisions of Geprek Express Samarinda city - Seto Indarto; Maimun Sholeh (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This article was created with the aim of identifying the influence of location and promotion on purchasing decisions at Geprek Express outlets in Samarinda, with a population of 258 people, where the sample in this study used 15% of the total population, namely 39 people. To get the data in this study, the author uses a questionnaire or a questionnaire, with a simple linear regression data analysis method and multiple linear regression analysis. The results of the partial calculation show that the T-count number has a lower number than the Ttable can be said that there is a joint influence of location and promotion on purchasing decisions at Geprek Express Gerai Bumi Sempaja outlets, Samarinda city. So marketing field of Geprek Express in Samarinda City to further increase promotional activities so that the products from Geprek Express are better known by the wider community so as to foster public interest in buying these products.